Community Based Learning: A Milestone of Health Science Students for their Academic and Professional Development - Chhetri, Muni Raj; Phuyal, Kamal; Amgai, Kapil (Journal of Karnali Academy of Health Sciences, 2021)
Community-based learning (CBL) is a teaching strategy that integrates academic coursework with community engagement. It connects academic theories and real-life problems at the community level. Students get an opportunity to learn academic content based on ground realities working in collaboration with community stakeholders. The main objective of CBL is to help both students and community stakeholders actively participate in the process to explore and understand the local realities which support them to learn from each other. It is an opportunity for community people to understand their problems as well as potentials in a more systematic and structured way that will help to develop plans for the positive change in society.1 Research has found that the community-based system of education makes students more enthusiastic, receptive and stimulating and help them to develop the sense of socially responsible.